Towards a Better Dacryocystorhinostomy, Evaluation of Multimodal Surgical Techniques in Nasolacrimal Duct Obstruction - Khudhair, Nadheer Hashim; Abdulaziz, Ahmed M.Hasan; Hasan, Loay Mahmod (AL-Kindy College Medical Journal, 2022)
Background: This study aimed to evaluate the outcome of long-term results of dacryocystorhinostomy (DCR) techniques in specialized eye care center in Iraq.Subjects and Method: This is a prospective study of 650 patients from July 2014 to July 2019 with nasolacrimal duct obstruction in Ibn Al Haitham Eye Teaching Hospital. A preoperative questionnaire was done, then one month, three months, six months and one year postoperatively. The success of surgery defined as follow; Absence of epiphora completely, Resolve of dacryocele or mucocele or any new attack of daryocystitis, Appearance of fluorescein dye from nose in fluorescein disappearance test, Successful irrigation of nasolacrimal duct which is proofed endoscopically. The three types of surgery (External, Endoscopic and Transcanalicular Laser DCR) were discussed to the patient then preferred one is chosen. The results and complication were recorded.Results: A total of 650 patients were included in this study, all were operated by same surgeon. The mean age of patients for external, endoscopic and Transcanalicular laser DCR (T-DCR) were 57, 44 and 51 years old respectively. The female patients were more than the male patients in all types of DCR surgeries and they represent 73.84% of total patients of external DCR (ext-DCR), 78.28% in endoscopic DCR (endo-DCR) and 55.15% in TCL-DCR. A satisfied patient to outcome according to surgery type was 91.20% with ext-DCR, 88.70% with endo-DCR and 51% with TCL-DCR.Conclusion: The most satisfied techniques to patients with higher success rate are the ext-DCR and endo-DCR while the TCL-DCR is still evolving with limit indications and lower success rate.